Kajian Etnobotani pada Masyarakat Adat Rongkong di Desa Rinding Allo Kecamatan Limbong Kabupaten Luwu Utara Sulawesi Selatan - Yuli Wartika; Eny Yuniati; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2013)
A Study Etnobotany within the Rongkong Villagers’ Traditions in Rinding Allo, the Sub-district of Limbong, Luwu Regency, South Sulawesi Province. This study employed explorative survey method. Data were gathered within the Rongkong villagers’ traditions dealing with the information on the utilization of plants used by the villagers. The objektive of this study was to find out the species of plants used by the villagers in their daily lives. This was a descriptive study to find out the value plant species adn employed qualitative approach with the similarity of Index Cultural Signifinance (ICS). The ICS was used to find out the index of important value of plants. It wasfound that were 101 species of beneficial plants and Oryza sativa L. was highest index of the species. Key words: Ethnobotany, useful plants, ICS indigenous peoples Rongkong